Media Integration of Islamic Sex Education for Early Childhood - Budi Sasono; Sunhaji Sunhaji; Rohmad Rohmad; Mohammad 'Ulyan; Mochammad Rizal Aufik (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Islamic sex education for early childhood uses the integration of important media taught in the digital era. This cannot be separated from the many cases of sexual violence that occur. This research aims to find out the use of media integration in the implementation of Islamic sex education for early childhood in Al-Hikmah Kindergarten Kutasari Purbalingga. This research is a qualitative research case study approach. Data collection techniques with semi-structured in-depth interviews, documentation, and direct observation. The study subjects were determined by snowball sampling techniques. Participants in the study were the Principal and 7 central teachers. Data analysis techniques using interactive data analysis models that is data reduction, data presentation, and withdrawal and testing of conclusions or verification. Testing the validity of data with the triangulation of sources and techniques. The results showed that the integration of Islamic sex education media for early childhood through central learning with the theme "My Body" increases children's knowledge to be more concrete about sexuality issues so as to stimulate child growth and development.